Classification of chiral fermionic CFTs of central charge $\le$ 16 - Philip Boyle Smith, Ying-Hsuan Lin, Yuji Tachikawa, Yunqin Zheng (SciPost Physics, 2024)
We classify two-dimensional purely chiral unitary conformal field theories which are defined on two-dimensional surfaces equipped with spin structure and have central charge less than or equal to $16$, and discuss their duality webs. This result can be used to confirm that the list of non-supersymmetric ten-dimensional heterotic string theories found in the late 1980s is complete and does not miss any exotic example.